SOSIALISASI TERHADAP PROSEDUR PENDIRIAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) DALAM MENINGKATKAN PENDAPATAN MASYARAKAT - Rohani, Siti; Asikin, Uti; Widiyastuti, Sri; Rachmawati, Rachmawati; Yaniza, Tiza; Sari, Devina Puspita (Jurnal Abdimas Bina Bangsa, 2024)
That partners still lack knowledge regarding the procedures for establishing Micro, Small and Medium Enterprises (MSMEs), which need to be paid attention to by partners, the implementation team feels they have to provide education regarding matters regarding procedures for establishing business entities to partners and the surrounding community. The method of implementing the activity is legal education and discussion related to the theme which is conveyed to the public, especially business actors who are members of MSMEs who have not legally registered their businesses in accordance with the provisions of the applicable laws and regulations. In the future, it is hoped that more MSME business actors will have legal awareness about how to set up a business entity so that they have legal certainty in carrying out their business activities. Then, with the continuation of this PKM activity using the same model, it can be applied to different MSMEs, and can even be expanded to MSMEs in other areas outside Kubu Raya Regency. It is also necessary to include other related parties, for example business groups, credit unions, banks and local governments, so that the scope of benefits of activities can be wider